2023
DOI: 10.2478/jofnem-2023-0020
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Commercial Cultivars of Kiwifruit to Infection by Root-knot Nematode and Its Biocontrol Using Endophytic Bacteria

Abstract: Root-knot nematodes (RKN) cause considerable economic losses to kiwifruit production annually. Screening of resistant cultivars has been one of the long-standing methods to manage root-knot nematodes. Here, the reaction of the four most common commercial cultivars of kiwifruit, namely, Actinidia chinensis var. deliciosa cv. Hayward, A. chinensis var. deliciosa cv. Abbott, A. chinensis var. deliciosa cv. Bruno, and A. chinensis var. chinensis cv. Haegeum (commonly known as ‘Golden’ kiwifruit) to infection by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Because these forages are used as direct feeding diets for livestock, toxic chemical nematicides may not be used. Newly discovered integration of resistant cultivars with BCAs can offer a novel eco-friendly strategy to control RKNs in kiwifruit orchards [ 36 ]. Moreover, recently published greenhouse tests demonstrated that grafting may alleviate the problems of these pathotypes.…”
Section: Proper Gene Pools and Scales Used To Determine Host Suscepti...mentioning
confidence: 99%
“…Because these forages are used as direct feeding diets for livestock, toxic chemical nematicides may not be used. Newly discovered integration of resistant cultivars with BCAs can offer a novel eco-friendly strategy to control RKNs in kiwifruit orchards [ 36 ]. Moreover, recently published greenhouse tests demonstrated that grafting may alleviate the problems of these pathotypes.…”
Section: Proper Gene Pools and Scales Used To Determine Host Suscepti...mentioning
confidence: 99%